PERDEBAAN POST-TRAUMATIC STRESS DISORDER PADAANAK DI DAERAH ALIRAN SUNGAI TONDANOPASCA BANJIR BANDANG KOTA MANADO (JURNAL KEPERAWATAN, 2014)
Abstrack: Introduction Post-traumatic stress disorder is a stressful experience that occurred as a result of disasters that may occur in every individual and children are vulnerable to get PTSD. Purpose of this study was to know charactheristics of age, gender and educationas well the different post-traumatic stress disorder in childrens in watershed tondano after flash flood in Manado. The design of this study using descriptive research design using a study group. Samples are 94 people. The data was collected by using questionnaire then the data were processed and analyzed by independent t-test with a significance level (Î±) of 0.05. based on the test results of the analysis using independent t-test P = 0.041 obtained value